2015
DOI: 10.1186/s12885-015-1837-1
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotegerin secreted by inflammatory and invasive breast cancer cells induces aneuploidy, cell proliferation and angiogenesis

Abstract: BackgroundOsteoprotegerin (OPG) is a glycoprotein that has multifaceted role and is associated with several cancer malignancies like that of bladder carcinoma, gastric carcinoma, prostate cancer, multiple myeloma and breast cancer. Also OPG has been associated with several organ pathologies. The widespread expression of OPG suggests that OPG may have multiple biological activities that are yet to be explored.MethodsThe anchorage-independent sphere cultures of the adherent cells were instrumental in our study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 76 publications
4
49
0
Order By: Relevance
“…Proteomic landscape of the breast cancer TME includes diverse factors involved in tumor growth, proliferation, metastasis, vascularity, evading cell death pathways and host immune system. In our previous study we demonstrated that inflammatory and invasive breast cancer TME is rich in OPG, chemokines such as urokinase-type plasminogen activator receptor (uPAR), Oncostatin M (OSM), IL-6 and GRO-α [6]. Here, we focus only on osteoprotegerin (OPG) as one of the factors present in the TME of inflammatory and invasive breast cancer cell lines, and discuss how it multitasks various functions to drive tumorigenesis.…”
Section: Tumor Microenvironmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteomic landscape of the breast cancer TME includes diverse factors involved in tumor growth, proliferation, metastasis, vascularity, evading cell death pathways and host immune system. In our previous study we demonstrated that inflammatory and invasive breast cancer TME is rich in OPG, chemokines such as urokinase-type plasminogen activator receptor (uPAR), Oncostatin M (OSM), IL-6 and GRO-α [6]. Here, we focus only on osteoprotegerin (OPG) as one of the factors present in the TME of inflammatory and invasive breast cancer cell lines, and discuss how it multitasks various functions to drive tumorigenesis.…”
Section: Tumor Microenvironmentmentioning
confidence: 99%
“…Our study [6] for the first time, revealed that OPG is secreted and expressed at very high levels from the SUM1315MO2 invasive breast cancer cell line, as well as the SUM149PT and SUM190PT inflammatory breast cancer cell lines. OPG was secreted at a concentration of 500 pg/ml and 1100 pg/ml from SUM1315MO2 and SUM149PT, respectively [6].…”
Section: Opg and Breast Cancermentioning
confidence: 99%
“…OPG plays a range of functional roles in cancer cell survival and progression, including tumor cell survival (56,65), TRAILinduced apoptosis resistance (66), cell phenotype, proliferation, and angiogenesis (67). Results from a study performed by Goswami and Sharma-Waila showed a consistently high OPG expression in infiltrating ductal carcinoma breast tissue samples when compared to control, uninvolved tissue samples (62). Moreover, when these results are taken together with other observations, it is proposed that OPG plays a major role in the angiogenic signature of aggressive breast tumor microenvironments (62).…”
Section: Discussionmentioning
confidence: 99%
“…Results from a study performed by Goswami and Sharma-Waila showed a consistently high OPG expression in infiltrating ductal carcinoma breast tissue samples when compared to control, uninvolved tissue samples (62). Moreover, when these results are taken together with other observations, it is proposed that OPG plays a major role in the angiogenic signature of aggressive breast tumor microenvironments (62). A study performed by Lane et al showed that OPG acts as a survival factor by protecting TRAIL-induced apoptosis of ovarian cancer cells (68).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation